Contribuições experimentais e numéricas da interação entre alvenaria de vedação e estruturas usuais de concreto armado - Amorim, Layane Silva de (Universidade Federal Rural do Semi-Árido, 2019)
This paper presents experimental and numerical contributions on the interaction between masonry of sealing and the usual structures of reinforced concrete. The main objective of this work was to contribute to the structural analysis of small reinforced concrete structures considering the interaction of the masonry of the fence. For this, the study consists of three analyzes by application of the finite element method: 1st mesh convergence, 2nd influence of beam stiffness and its effects on masonry and 3rd influence of the relationship between height and length of the portal and its masonry effects. It was concluded that, within the discretized meshes that represents the reality using a lower computational cost is the mesh of 20x20 and that for structures of small reinforced concrete masonry does not present great contribution in the rigidity of the portico.
Monografia
Keywords: Alvenaria; Prismas; Pórtico; Masonry; Prisms; Portico; ENGENHARIAS::ENGENHARIA CIVIL